The Symmetric and Asymmetric Effects of Governance on Natural Resources Dependence in GCC Countries - Alrubaye, Ali Ayad Hasan; Abd Ghani, Judhiana; Kamarudin, Ainatul Aqilah; Al-Jubouri, Amir Makhif (Advances in Social Sciences Research Journal, 2026)
The current study examined the symmetric and asymmetric effects of governance quality on natural resource dependence in the Gulf Cooperation Council (GCC) countries from 1996 to 2023. Governance quality was measured using a composite index derived from the Worldwide Governance Indicators, recording institutional effectiveness, regulatory quality, and control of corruption. The analysis applied the Pooled Mean Group (PMG) and Dynamic Common Correlated Effects (DCCE) estimators using panel data techniques to identify long-term relationships while accounting for heterogeneity and cross-sectional dependence. Furthermore, a Nonlinear Autoregressive Distributed Lag (NARDL) model was employed to document asymmetric dynamics. The results revealed that improvements in governance generate statistically significant and economically meaningful reductions, depending on natural resource rents, by strengthening institutional capacity and supporting economic diversification. Conversely, population growth, inflation, and exchange rate volatility raise natural resource dependence by intensifying fiscal pressures and macroeconomic instability, while economic growth consistently mitigates reliance. Therefore, governance improvements yield stronger and more persistent reductions in resource dependence than those associated with governance deterioration, emphasising the importance of sustained institutional reform and macroeconomic stability for GCC diversification strategies